Stakeholder and end-user perspectives to refine the Context-sensitive Positive Health Questionnaire (CPHQ) to measure broad health - Mirte Boelens; Cheryl Roumen; Esther J. Bloemen-van Gurp; John Dierx; Lenny Nahar-van Venrooij; Tim van Zutphen; Pien M.R. Christiaanse; Jaron Schnitzer; M. Elske van den Akker-van Marle; Miriam J.J. de Kleijn; Marja van Vliet; Jessica C. Kiefte-de Jong; et al. (PLOS One, 2026)
Introduction Broad health concepts are increasingly embedded in healthcare and other domains. Therefore, in a previous study, we developed and validated the Context-Sensitive Positive Health Questionnaire (CPHQ). The CPHQ is based on Positive Health, the Capability Approach and on perspectives of stakeholders and end-users, including those with a lower socioeconomic position (SEP) with the aim to validly measure broad health. Stakeholders and end-users were involved in the development process. However, professionals working in healthcare, welfare or policy domain were not sufficiently involved, while their perspective on how to measure broad health is needed to support broader applicability and acceptability. Objective We aimed to refine the 32-item CPHQ for cross-domain use through focus group discussions (FGDs) with stakeholders across healthcare, welfare and policy domains, researchers, as well as patients and citizens, including those from a lower SEP, expert review and a member check. Methods We conducted nine (FGDs) and one interview with stakeholders from healthcare, welfare, and policy domains, research, patients and (lower SEP) citizens (n = 76). An adapted COMET method analysis and qualitative analysis were used, followed by a member check to validate the changes. Results Items were omitted, merged or added, leading to a refined CPHQ (28 items). Main themes guiding edits were 1) the importance of avoiding normative phrasing and including subjectively interpretable items, 2) prioritization of items reflecting aspects of experienced health (e.g., “I feel happy” or “I feel healthy”), 3) relevance of functionings. At the same time, views diverged on the inclusion and wording of items related to exclusion, political representation and sense of belonging. These items were subsequently discussed by the core group and evaluated using the predefined decision rules and qualitative feedback. Conclusion The CPHQ refinement involved a wide range of stakeholders, including end-users. This led to a 28-item CPHQ to measure broad health. Future research in different populations and settings is needed to validate and possibly shorten the refined CPHQ.